4z+3-9x=

Simple and best practice solution for 4z+3-9x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4z+3-9x= equation:


Simplifying
4z + 3 + -9x = 0

Reorder the terms:
3 + -9x + 4z = 0

Solving
3 + -9x + 4z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -9x + -3 + 4z = 0 + -3

Reorder the terms:
3 + -3 + -9x + 4z = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -9x + 4z = 0 + -3
-9x + 4z = 0 + -3

Combine like terms: 0 + -3 = -3
-9x + 4z = -3

Add '-4z' to each side of the equation.
-9x + 4z + -4z = -3 + -4z

Combine like terms: 4z + -4z = 0
-9x + 0 = -3 + -4z
-9x = -3 + -4z

Divide each side by '-9'.
x = 0.3333333333 + 0.4444444444z

Simplifying
x = 0.3333333333 + 0.4444444444z

See similar equations:

| 2k+9k= | | 8x+8=2x+3 | | y=2xy+6y-10 | | 16.95=1/x | | 5(4+2x)+2x=176 | | 3+2m-7=10 | | Y2=-1/4x | | 9x-(2x-10)=40 | | 0.5=8/x | | 4(x+6)=20x-7 | | X=112+-3x | | 7x=-26 | | 3x=146 | | 4x+24=2x-7 | | 45c^6+20c^4= | | 10xy+8x+25y+20=0 | | 6y-9=3(y+5) | | 15x+64=302 | | 7d=-21 | | 0=9x-56 | | 7t-9=3(y+5) | | (7u-5)^1/2=(9u-15)^1/2 | | 3x+63=84 | | y=-px+q | | 0.09Xx=144.39 | | 19=x-y | | 5(t-2)=1+10 | | 30=5(x+10) | | x+b+c(m)=x | | 3400=x^2+60x+1800 | | 1x=x | | 3x^2-5x-99=0 |

Equations solver categories